Target Text Contraction in English-into-Korean Translations: A Contradiction of Presumed Translation Universals? - Cheong, Ho-Jeong (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis paper contradicts the prevailing assumptions among the advocates of translation universals (TU’s) that explicitation, a translation behavior which consists of spelling things out rather than leaving them implicit in translation, is a potential TU, irrespective of the specific language pairs involved in the process of translation. Specifically, via a study employing a newly built 517,609-word parallel corpus, it is shown that implicitation and the subsequent TT contraction as well as explicitation and TT expansion entailed were both observed in translations involving Korean and English. The significance of the direction of language combinations in translations employing the same language pair was identified, together with the introduction and verification of the validity of the four measurement units devised for this study to capture diverse aspects of explicitation/implicitation which in turn entail TT expansion/contraction.